2018
DOI: 10.3390/toxins10100420
|View full text |Cite
|
Sign up to set email alerts
|

Identification of Causative Ciguatoxins in Red Snappers Lutjanus bohar Implicated in Ciguatera Fish Poisonings in Vietnam

Abstract: Ciguatera fish poisoning (CFP) is a type of food poisoning caused by the consumption of a variety of toxic ciguatera fish species in the tropical and subtropical waters. Although there have been a large number of suspected CFP cases in the Southeast Asian countries, few were confirmed with causative ciguatoxins (CTXs), and reliable information on the symptoms still remains rather limited. In the present study, CTXs in red snapper Lutjanus bohar, implicated in two suspected CFP cases in Vietnam in 2014 and 2016… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
16
2

Year Published

2019
2019
2023
2023

Publication Types

Select...
10

Relationship

1
9

Authors

Journals

citations
Cited by 20 publications
(20 citation statements)
references
References 31 publications
2
16
2
Order By: Relevance
“…The CTX-1B concentration detected in sample "Head 2" of L. bohar was 0.38 ng/g tissue, which expressed 5.40 MU/100 g tissue of toxicity. Although CTX-1B was also detected in "Head 5", the amount was below the LOQ (limit of quantification) (0.32 ng/g fish flesh) reported in our previous paper [31].…”
Section: Toxin In Fish Samplescontrasting
confidence: 64%
“…The CTX-1B concentration detected in sample "Head 2" of L. bohar was 0.38 ng/g tissue, which expressed 5.40 MU/100 g tissue of toxicity. Although CTX-1B was also detected in "Head 5", the amount was below the LOQ (limit of quantification) (0.32 ng/g fish flesh) reported in our previous paper [31].…”
Section: Toxin In Fish Samplescontrasting
confidence: 64%
“…preferred algal host substrates. Unlike what is observed in other CP endemic areas such as the Indian Ocean, the Caribbean, the eastern Atlantic Ocean, and the western Pacific [95][96][97][98][99], where CP events rarely involve herbivorous species, Scaridae, Acanthuridae, and Kyphosidae are frequently reported in CP cases occurring in French Polynesia and the Cook Islands [10,50,75,100]. By way of example, between 2008 and 2018, herbivorous species consistently ranked among the top five species most frequently involved in CP cases recorded annually in French Polynesia (www.ciguatera.pf [63]).…”
Section: Discussionmentioning
confidence: 58%
“…The complexity of the matrix and the difficulty in the ionization of CTXs also jeopardizes the applicability of LC-HRMS for the detection of CTXs. Despite this, the applicability of HRMS has been demonstrated in particular for CTX1B and CTX3C as the main toxins responsible of CP in the Pacific Ocean, the fragmentation pathways have been identified, increasing the knowledge on how these complex toxins fragment in the mass spectrometer [17][18][19]. Recent studies published by Kryuchkov et al [20] reported strategies for the structure elucidation of Caribbean ciguatoxin analogues (C-CTX3 and C-CTX4).…”
Section: Introductionmentioning
confidence: 99%